Communism In India - "Sharma, T.R." (New Delhi, 1984)
On the basis of intensive study of inner-party documents and other primary source material, the present volume highlights the nature of intense but latent intra-party differences which existed in the Communist Movement in India from 1947. The multi-structural nature of economy and fragmented nature of society rendered the formation of classes difficult, making it impossible for the left to have a correct and cogent assessment of Indian socio-economic reality. The situation was further complicated by the complex nature of Indian bourgeoisie who intelligently combined the tasks of national liberation, revolutionary transformation, and capitalist formation. Consequently, the pendulum of communists' strategy towards the bourgeoisie kept swinging back and forth from complete unity to complete struggle with numerous intermediate positions. This ultimately led to the gradual fragmentation of the communist movement. The Sino-Indian border war of 1962 and the Sino- Soviet ideological schism accelerated this process. The imperatives of electoral politics reinforced this factionalism and power rivalry in the party pushing it from split to split.
Keywords: Communism